Early high‐dose continuous veno‐venous hemofiltration alleviates the alterations of CD4+ T lymphocyte subsets in septic patients combined with acute kidney injury. Issue 7 (17th February 2022) - Jin, Beibei; Cao, Da; Yang, Ning; Wang, Ling; Li, Ruifang; Liu, Xiumei; Gong, Ping
Abstract: Background: This study aims to determine whether early high‐dose continuous venous–venous hemofiltration (CVVH) alleviates the alterations in CD4 + T lymphocyte subsets in septic patients combined with acute kidney injury. Methods: Enrolled septic patients combined with acute kidney injury were randomized into CVVH ( n = 50) and conventional treatment (non‐CVVH, n = 53) groups. Healthy volunteers ( n = 21) were enrolled. CVVH was initiated within 12 h of intensive care unit (ICU) admission with doses of 35 60 ml/kg/h and maintained for at least 72 h. Th1, Th2, Th17, and Treg were measured by flow cytometry on days 1, 3, and 7 of ICU admission. Sequential organ failure assessment (SOFA) scores were calculated. Results: Th1 percentages and Th1/Th2 ratios were lower, and Th2, Th17, and Treg percentages and Th17/Treg ratios were higher in s eptic patients compared to healthy volunteers. CVVH significantly increased Th1 percentages and Th1/Th2 ratios, and significantly decreased Th2, Th17, and Treg percentages and Th17/Treg ratios compared to non‐CVVH. Th1 percentages and Th1/Th2 ratios were negatively correlated with SOFA scores, while Th2, Th17, and Treg percentages and Th17/Treg ratios were positively correlated with SOFA scores. Patients with CVVH had significantly lower SOFA scores on day 7 of ICU admission and a shorter ICU stay compared to those with non‐CVVH. Conclusions: Septic patients combined with acute kidney injury exhibit different alterations of CD4 + T lymphocyte subsets. Early high‐dose CVVH alleviates the alterations, which may be one of the factors associated with improved sepsis severity. Abstract : Septic patients combined with acute kidney injury exhibited decreased Th1 percentages and Th1/Th2 ratios, and increased Th2, Th17 and Treg percentages and Th17/Treg ratios; early high‐dose continuous venous‐venous hemofiltration (CVVH) alleviated these alterations. Th1 percentages and Th1/Th2 ratios were negatively correlated with sequential organ failure assessment (SOFA) scores, while Th2, Th17 and Treg percentages and Th17/Treg ratios were positively correlated with SOFA scores. Patients with CVVH had significantly lower SOFA scores and a shorter ICU stay.